Aluminas macro-mesoporosas produzidas pelo método sol-gel para aplicação em catálise heterogênea - Passos, Aline Ribeiro [UNESP] (2015)
Alumina is an important support for heterogeneous catalysts. The matching of appropriate alumina physical properties and controlled textural properties can improve its performance as support in catalysis applications. Cobalt based catalysts have been reported to have a good ethanol steam reforming (ESR) performance due to their high activity for the cleavage of C-H and C-C bonds. Many studies have been conducted about the effects of alumina properties on the cobalt catalysts properties. Alumina exhibits a rather complex surface chemistry which can be controlled by the preparation procedure. In this work alumina samples with macro and mesoporous structure were obtained using the one-pot sol-gel synthesis accompanied by phase separation. In this integrative strategy both processes, gelation and phase separation, spontaneously occur in system containing the presence of the phase separation inducer. The different aluminas were produced by using as aluminum reactants, aluminum isopropoxide and chloride and polyethylene oxide or polypropylene oxide as phase separation inducer. Appropriate choice of the starting composition allows the control the pore size and volume. Macroporous are formed as a result of phase separation after burning the phase separation inducer, while voids between particles of the xerogel skeletons form a mesoporous structures. The different alumina porous alumina and commercial alumina were used as supports for preparing by wetness impregnation cobalt-based catalyst. The oxidic catalyst precursors obtained after calcination are composed of Co3O4 and CoAl2O4-like phases, the latter being in higher proportions in the sol-gel alumina than in the commercial one. As the sol-gel alumina presents a larger amount of octahedral AlVI sites and surface hydroxyl groups than the commercial alumina, it was assumed that these features can facilitate the migration of Co ions into the alumina network...